(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to examine the theoretical foundations of the International Sustainability Disclosure Standard (IFRS S1), issued by the IFRS Foundation, which sets out the general requirements for disclosing sustainability-related financial information. It also explores the impact of sustainability disclosure on users’ decisions and reviews key aspects of local accounting rules No. (6) and (10) related to the disclosure of financial statements and accounting policies for banks and similar financial institutions. The study relies on analysing relevant international accounting rules and standards, proposing a model for the annual management report that incorporates the key elements of IFRS S1. This model can be applied across various economic units to assess its impact on users’ decisions. The findings indicate that local accounting rule No. (6) has not been updated to incorporate the sustainability requirements outlined in IFRS S1, highlighting the need for legislative reforms to enhance sustainable financial disclosure. The study recommends adopting the proposed annual management report model to improve the quality of financial disclosures and support better decision-making for users.